Knowledge regarding dental ergonomics and the occurence of musculoskeletal disorders in students at Hasanuddin University Dental Hospital, Indonesia: Pengetahuan tentang ergonomik dental dan terjadinya gangguan musculoskeletal pada mahasiswa di Rumah Sakit Gigi Mulut Universitas Hasanuddin, Indonesia - Fuad Husain Akbar (Makassar Dental Journal PDGI Makassar, 2021)
Background: Musculoskeletal disorders (MSDs) are complaints that are felt when muscles receive static loads repeatedly for a long time, causing disorders in the form of damage to joints, ligaments and tendons. Objective: To determine the relationship between the level of knowledge about dental ergonomics and the occurrence of MSDs in students at Dental Hospital Hasa-nuddin University. Methods: This analytic observational study with a cross-sectional design included 83 dental interns and re-sidents. Assessment of MSDs were derived from Nordic body map (NBM) and a 10-items questionnaire was used to determine the level of knowledge regarding dental ergonomic. Data were analysed with the Spearman correlation test and Pearson chi square test. Results: The Spearman correlation test shows a value of 0.000 (p<0.05), which means that there is a significant relationship between ergonomic knowledge and the occurrence of MSDs among the respondents. Conclusion: Level of know-ledge regarding dental ergonomics, age, education, and the duration of work related with the occurrence of musculoskeletal disorders in residents and dental interns.